1995
DOI: 10.1016/0014-5793(95)00145-y
|View full text |Cite
|
Sign up to set email alerts
|

Thermodynamic and functional characterization of a stable IgG conformer obtained by renaturation from a partially structured low pH‐induced state

Abstract: At pH 2, rabbit lgG adopts a partially structured state that exhibits loss of thermal unfolding transition, tentatively assigned to the CH2 domain, whilst retaining a well-defined tertiary structure for the rest of the molecule and extensive secondary structure. Renaturation of lgG from this state yields a stable conformer that differs from native lgG by a lower degree of interaction between the CH2 and CH3 domains, and stronger interaction between the CHI and CH2 domains, as judged by differential scanning ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
44
0

Year Published

1997
1997
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(48 citation statements)
references
References 13 publications
4
44
0
Order By: Relevance
“…Although we cannot currently identify the precise binding site of the type II peptide, the previous papers described the suggestive but controversial results that the domain is affected by acid treatment. Martsev et al proposed that the CH2 domain of rabbit IgG is destroyed by acid treatment (16). In contrast, Thies et al who used the isolated CH3 domain of murine IgG, demonstrated that the CH3 domain could possess an alternative conformational state induced by acidic pH (23).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Although we cannot currently identify the precise binding site of the type II peptide, the previous papers described the suggestive but controversial results that the domain is affected by acid treatment. Martsev et al proposed that the CH2 domain of rabbit IgG is destroyed by acid treatment (16). In contrast, Thies et al who used the isolated CH3 domain of murine IgG, demonstrated that the CH3 domain could possess an alternative conformational state induced by acidic pH (23).…”
Section: Discussionmentioning
confidence: 99%
“…Protein A (16). Recently, Ejima et al studied the effects of acid exposure on conformational changes in human IgG4 and showed that the molecular species of the non-denatured structures with limited structural changes are generated by exposure to pH 2.7-3.9 by CD and differential scanning colorimetry (14).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…All of these functions unfolding studies have been carried out for whole antibodies and their fragments, since they consist of simply must be intact in order for Abs to work in Western blot analysis and immunoprecipitation experiments. The 12 independent folding units termed immunoglobulin domains (4)(5)(6)(7)(8)(9)(10)(11)(12)(13). Domain folding and domain/domain observed activities of refolded protein from the glycine-, urea-, and GdnHCl-eluted pools indicate native interactions during unfolding and refolding can be…”
Section: Figmentioning
confidence: 99%